O anachroniczności polskiego kapitalizmu – niekonserwatywne krytyki liberalizmu we współczesnej Polsce - Chwedoruk, Rafał (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2003)
The great political transformations in Poland after 1989 have made the notion of broadly understood liberalism the core of political discourse. There have emerged frequent claims of significant or even critical influence of this idea on the model of social, economic and political reforms. At the same time, an increasing discrediting trend of varied origins has emerged. The purpose of this paper is to present the key themes of critics of liberalism speaking from a pro-modernization point of view, i.e. those who accept the broadly understood Enlightenment paradigmand approve the imperative civilization modernization of Poland by means of its occidentalization. The discourse of liberal reformers with their opponents to a certain degree reflects the mythological dichotomy of the left and the right, although not many participants in the dispute have necessarily had to identify themselves in this respect.